The introduction of dependent interviewing on the British Household Panel Survey - Annette Jäckle; Heather Laurie; S.C. Noah Uhrig (University of Essex, Institute for Social and Economic Research (ISER), 2007)
This paper documents the introduction of dependent interviewing in wave 16 of the British Household Panel Survey (BHPS). Dependent interviewing is a method of designing questions on longitudinal surveys where substantive information, available to the survey organisation prior to the interview, is used to tailor the wording and routing of questions to the respondents situation or to enable in-interview edit checks. The decision to introduce dependent interviewing in the BHPS was motivated by data quality issues and the paper discusses the reasoning behind this decision. A particular aim was to reduce measurement error that leads to cross-wave inconsistencies and hence biases in estimates of change, such as seam effects in histories of employment or benefit receipt. The paper provides documentation for BHPS data users and outlines the implications of the changes made when using the data. The paper also provides information about the questionnaire design, testing process and technical aspects of the implementation, for survey practitioners and methodologists who may be considering implementing dependent interviewing on a longitudinal survey.
Keywords: 330